Revealing diversity patterns of vascular plants and their causes in semiarid high mountain regions. A top-down approach for Great Basin mountain ranges, USA - Grüninger, Friederike; Fickert, Thomas (ERDKUNDE, 2003)
Revealing diversity patterns of vascular plants and their causes in semiarid high mountain regions - a top down approach for Great Basin mountain ranges, USA. Biodiversity, or the richness of living organisms within a particular area, always has to be seen in dependency to the scale of observation. The mechanisms and processes influencing diversity are often not equally effective and / or visible on different scales, hence a multi-scale approach is indispensable for explaining existing diversity patterns. This study tries to reveal patterns and causes of vascular plant diversity in semiarid mountain Ranges of the Great Basin by using the four following observation scales: - the landscape-scale covers the hole region of the Great Basin with its single mountain ranges; - the mountain-scale considers one particular mountain range with its altitudinal belts along environmental gradients; - the belt-scale is employed to describe structural patterns within climate induced altitudinal vegetation belts of a mountain range; - the patch-scale regards the different environmental units formed by dynamic processes within the essential communities of the various belts.